When Does a Child ‘Participate Actively in Hostilities’ under the Rome Statute? Protecting Children from Use in Hostilities after Lubanga - Yuvaraj, Joshua (Utrecht Journal of International and European Law, 2016)
This paper explores the scope of activities children may engage in for a defendant to be convicted for using them to participate in hostilities under the Statute of the International Criminal Court (ICC). It analyses the relevant international law provisions and the ICC’s decisions in the Lubanga matter. It finds that a broad scope of activities more effectively assists the protection of children from use in hostilities. It also identifies inconsistencies in the relevant international law provisions and proposes a number of factors future ICC Chambers can use to consistently characterise activities in future prosecutions.